Does the Artist Need to Be Present? The “Paradigm of Visibility” and Art Practices in Public Space - Białkowski, Łukasz (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2017)
The thesis of my paper is that art participatory practices in public space have a paradoxical potential to avoid a paradigm of visibility. What I call the paradigm of visibility is a formula of social presence of art which is based on a necessity of occupying a certain physical or symbolical space and an effort to sustain it. This kind of public presence of art is traditionally considered to be a guarantee of its value in terms of both artistic and social legitimisation. A question arises if this formula has an alternative. It seems that participatory art practices in public space – focused on production of objects and searching for social impact and social efficacy – can formulate a different model of presence of art (of its production and distribution) than object-based art.